Recurrence rate and predictors in non-ischemic reversible bradyarrhythmias - Dwivedi, Sudhanshu Kumar; Sharma, Akhil Kumar; Agrawal, Anant; Doomra, Kapil; Chaudhary, Gaurav Kumar; Chandra, Sharad; Bhandari, Monika; Vishwakarma, Pravesh; Pradhan, Akshyaya; Sethi, Rishi; Shukla, Ayush; Singh, Abhishek; et al. (Frontiers in Cardiovascular Medicine, 2024)
Objective: Non-ischemic symptomatic reversible bradyarrhythmia is a poorly characterized common clinical challenge. This study aimed to assess the incidence and predictors of recurrence and need for permanent cardiac pacing in patients with non-ischemic symptomatic reversible bradyarrhythmia.Methods: Prospective single-center study of consecutive 124 adult patients presenting with non-ischemic symptomatic reversible bradyarrhythmia who were followed up for up to 24 months after conservative management during index hospitalization. Primary endpoint was a recurrence of bradyarrhythmia requiring permanent cardiac pacing. Secondary endpoint was a composite of recurrence requiring permanent pacing, readmission, or death. Univariate and multivariate analyses were done to determine the predictors of the endpoints.Results: Sinus node and atrioventricular node disease was seen in 66.1% and 33.9% patients, respectively. Most common causes for bradyarrhythmia were negative chronotropic drugs (58.1%) and hyperkalemia (55.6%). Permanent pacing was required in 21.8% patients after a recurrence. Advanced atrioventricular block at presentation (HR: 6.10, 95% CI: 2.45-15.20, p <0.001) and bifascicular block at discharge (HR: 3.63, 95% CI: 1.58-8.33, p=0.002) during index hospitalization were significant independent predictors of recurrence requiring cardiac pacing.Non-ischemic symptomatic reversible bradyarrhythmia is associated with a high risk of recurrence. Permanent cardiac pacing should be considered during index hospitalization in patients with advanced atrioventricular block and/or bifascicular block.